Differences between reaction time to stimulus onset and offset: Evidence for post-perceptual effects - Sokolova, R.; Rukšėnas, O.; Burle, B. (Psichologija, 2013)
Reaction time to stimuli offset is usually longer than to stimuli onset (offset disadvantage). According to V. Di Lollo et al. (2000), such disadvantage arises from the need to suppress the automatically arisen response to stimulus onset that necessarily precedes the offset. If such is the case, one expects the onset–offset difference to decrease as the delay between stimulus onset and offset (i.e. foreperiod) increases. Results of the first experiment confirmed this hypothesis. A potential confounding factor was identified, however, related to different sensory consequences after the response (i.e. light offset vs. light onset in the reaction time to stimulus onset and offset tasks, respectively). We thus reasoned that, besides suppression, the action effect could influence the results. Results of the second experiment in which the sensory consequences were equalized confirmed the role of the action effect and suggest that, when such an effect is removed, suppression plays a little role in offset disadvantage.
Keywords: reaction time; stimulus onset; stimulus offset